Toxicological Assessment of Nannochloropsis Oculata Microalgae in Rats - Kafaie, Soroush (2011)
Nannochloropsis oculata is a green unicell microalgae with valuable ingredients.Despite this, some of them are harmful for humans and animals. The chief route of human and animal exposure to the effects of these microalgae is food, especially that derived from aquatic origins. The major toxicity effects of harmful microalgae are associated with their production of toxins and bioaccumulation of heavy metals. The aims of this study were to determine the mineral composition of Nannochloropsis and to investigate acute and sub-chronic toxicity of Nannochloropsis oculata. The mineral content of Nannochloropsis oculata was assayed using a Flame Atomic Absorption Spectrometry (AAS) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Mineral analysis showed that Nannochloropsis oculata did not bioconcentrate high amounts of heavy metals. In the acute study, twelve Sprague-Dawley rats of both sexes were gavaged with 12 g/kg body weight of Nannochloropsis oculata one time and then tested for morbidity and mortality in 14 days. Rats had free access to food and water in these two weeks. Blood samples were drawn before treatment and kept as a control for later analysis. Results of the acute study revealed that the oral LD50 of Nannochloropsis oculata in rats was greater than 12 g/kg body weight since no toxicity effects were observed on Nannochliropsis oculata in terms of morbidity signs, plasma biochemical parameters, organ tissue, or body weight gain. In the sub-chronic study, thirty six Sprague-Dawley rats of both sexes were chosen and divided into three groups; a control group and two treatment groups. These groups were provided with diet containing respectively 0, 3, and 6 g/kg body weight of Nannochloropsis oculata every early morning and then allowed free access to normal food and water ad libitum for 60 days. The results of the sub-chronic study demonstrated that in comparison with the control group, no biologically significant effects of Nannochloropsis oculata were observed on organ weights, male body weight gain, or on the plasma biochemical parameters. However, low creatinine and significant differences in body weight gain by female rats were noted in the treatment groups. Histopathology examination of male and female rat livers and kidneys did not disclose any adverse effects. In addition, no significant differences were found in the antioxidant activities between the treatment groups and the control one; the antioxidant activity of plasma was evaluated using the Ferric Reducing Ability of Plasma (FRAP) and ABTS methods. In summary, it could be concluded that exposure of growing rats of both genders to Nannochloropsis oculata at dosages up to 12 g/kg of body weight is non-toxic.